2017
DOI: 10.4103/ijpm.ijpm_810_15
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma arising from renal capsule: An extremely rare entity

Abstract: Malignant fibrous histiocytoma (MFH) usually presents in the extremities or retroperitoneum. MFH arising from renal parenchyma or renal capsule is extremely rare, only few cases have been reported in literature and portend a poor prognosis. Renal MFH is differentiated from renal cell carcinoma, renal sarcoma, and sarcomatoid renal tumor only by histological and immunohistochemical studies. Since the therapeutic options for MFH are different, its early diagnosis is imperative. Herein, we report a case of a prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The diagnosis of UPS mainly depends on path morphology and immunohistochemistry. UPS is characterized by a typical immunopositive response to CD68 and vimentin, which distinguishes it from other renal sarcomas (Bairwa et al 2017). The CT scan of renal UPS showed a large solid tumor, usually with necrotic or hemorrhagic areas and adjacent invasion, and the attenuation on enhanced CT scan was slightly higher than that of skeletal muscle (Karaosmanoğlu et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis of UPS mainly depends on path morphology and immunohistochemistry. UPS is characterized by a typical immunopositive response to CD68 and vimentin, which distinguishes it from other renal sarcomas (Bairwa et al 2017). The CT scan of renal UPS showed a large solid tumor, usually with necrotic or hemorrhagic areas and adjacent invasion, and the attenuation on enhanced CT scan was slightly higher than that of skeletal muscle (Karaosmanoğlu et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Neoplasms originating in the renal capsule are very rare. Among fibrohistiocytic tumors, BFH [5] and malignant fibrous histiocytoma(MFH) [6, 7] have been described in the literature. Shoji K. et al first reported a case of BFH originating in the renal capsule in 1992 [5], measuring 6 × 4.5 × 6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneum or kidney origin accounts for 12–14% of all cases [14]. There are few reported cases of MFH definitely arising from the renal capsule [6, 7, 15, 16]. The histology characters of MFH were groups of histiocytes and pleomorphic giant cells with large nuclei and moderate mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, MFH is divided to five types, including storiform-pleomorphic, myxoid, giant cells, inflammatory and angiomatoid [9, 29, 30], among which the storiform-pleomorphic type is the most usual and commonly high grade variant of MFH [24, 31]. MFH is characterized by typical immunepositivity for CD68, vimentin and alfa-1-antitrypsin that can differentiate it from other renal sarcomas [29] and among these markers, CD68 has become as a specific histological marker for confirming MFH [32]. Our case was also consistent with storiform arrangement of spindle cells admixed with mononuclear to multinucleated giant cells and histiocytic cells known as a histological hallmark of MFH [33] and the diagnosis was confirmed by immunohistological staining.…”
Section: Discussionmentioning
confidence: 99%